MOLD DESIGN AND FLOW ANALYSIS FOR PRODUCT PROPELLER APC SF 11X4.7 WITH MINIMUM SHRINKAGE AND WARPAGE - Sahputra, Wahyu Puji; Budiyantoro, Cahyo; Nugroho, Gesang; Adam, Muhammad Kevin (Jurnal Rekayasa Mesin, 2024)
Making molds in the injection molding manufacturing process is one of the basic steps that functions to prevent product defects during the production process. The product defects that most often occur in this manufacturing process include shrinkage and warpage defects. This research will discuss the mold design for the APC SF 11x4.7 propeller product with a twist variation of 45o and minimum shrinkage and warpage values. Glass Fiber Reinforced Polypropylene (GFRPP) will be used as the propeller product material. The entire design process to testing will be carried out using software assistance. The Taguchi method with an L9 orthogonal array matrix (34) was used in this research. where L9 explains that the experiment will be carried out nine times, and 34 means there are three levels and four main factors. The four main factors consist of packing pressure, packing time, melting temperature and injection pressure. The Taguchi method is used with the aim of making it easier to find the variation value that produces the lowest shrinkage and warping defects in the product. The simulation results show that the variation with the smallest shrinkage value produces a value of 7.9% and the variation with the smallest warpage value produces a value of 1.051 mm